(untitled) (Global Journal of Human-Social Science, 2021)
The process of L2 (Second language) acquisition is a complicated, conscious one that requires an understanding of L2 input to produce L2 output. Among different strategies, Negotiated Interaction is one way to improve L2 acquisition. Though Bangladesh is a monolingual country, in education system of Bangladesh, English plays an important role. Especially in tertiary education in Bangladesh, English is the dominating medium of teaching and learning. Tertiary education is the level after which usually students in Bangladesh go for searching different types of jobs, so Negotiated Interaction can be helpful to keep a balanced atmosphere of input and output for both the teachers and learners. Apart from some limitations, this strategy can be one of the most effective one in case of teaching and learning in the tertiary education in Bangladesh. The purpose of this article is to show how this strategy improves L2 acquisition. Negotiated Interaction can play an effective role in combining teaching and learning processes for L2 acquisition in tertiary education in Bangladesh.